Study on the Use of Social Media in Islamic News Production of Harian Umum Duta Masyarakat - Hakim, Lukman; Filjannah, Khildah; Aziz, Moh. Ali (Proceedings of International Conference on Da'wa and Communication, 2020)
The presence of social media offers convenience to interact, share content and communicate with other users. The use of social media in everyday life is common. Likewise, several mass media journalists have begun to use social media in the process of producing news. This research was conducted to find out what social media is used, what are the attitudes of journalists, and the extent to which social media is used in the production of Islamic news at Duta Masyarakat. This research uses qualitative research methods and case study research types. The data collection technique was carried out by observation, interviews with the Chief Editor, the Editor, and four journalists from the Community Ambassador, as well as related documents. The results of this study explain that the social media used are Twitter, Facebook, Instagram and Whatsapp. Journalists' considerations Community Ambassadors use social media in their news production because social media stores a lot of information and can reach information that journalists have missed. In the process of producing Islamic news, social media is used at the news planning stage, namely to monitor information, find references, determine angles, and become news sources. Furthermore, at the news search stage, social media is used to interview sources and share photos with sources.